2017
DOI: 10.4103/0971-4065.177208
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia - A rare complication of Gitelman's syndrome

Abstract: Gitelman's syndrome (GS) is a rare autosomal recessive disorder caused by mutations in thiazide-sensitive NaCl cotransporter. We report a 49-year-old, normotensive lady with prolonged hypokalemia since her 20s who was diagnosed with GS at our renal clinic. During follow-up, she was found to have mild, asymptomatic, euvolemic hyponatremia with low serum uric acid, inappropriately high urine osmolality and sodium consistent with syndrome of inappropriate antidiuretic hormone-like presentation. Despite life-long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…An extensive review of literature revealed only three cases reported until now, being first reported by Schepkens et al 21 in two patients in 2001. In light of these cases, the presence of hyponatraemia may be attributed to the multifaceted, intricate interplay between life-long tubular salt wasting, antidiuretic hormone hyper-secretion owing to extracellular volume depletion, and diminished diluting function of the distal tubules 22. When present, it induces symptoms such as headache, nausea and mental confusion.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive review of literature revealed only three cases reported until now, being first reported by Schepkens et al 21 in two patients in 2001. In light of these cases, the presence of hyponatraemia may be attributed to the multifaceted, intricate interplay between life-long tubular salt wasting, antidiuretic hormone hyper-secretion owing to extracellular volume depletion, and diminished diluting function of the distal tubules 22. When present, it induces symptoms such as headache, nausea and mental confusion.…”
Section: Discussionmentioning
confidence: 99%